The Effect of Drill Form To The Wall on The Accuracy of Passing The Inside Foot of PERBI FC Football Players - Ahmad Rizaldi Salmanulloh; Adang Sudrajat; Dewi Susilawati (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study aims to solve the problem of drill training forms on the accuracy of passing the inner foot so that players have good passing quality and are right in the direction of the ball's goal. The sample of this study is PERBI FC Football players in the Bandung Regency area. The number of samples of this study is 30 PERBI FC players, this research test consists of 1 type, namely the inner foot passing accuracy test where the accuracy of passing must be measured, and the passing accuracy test with a distance of 10 meters. Lack of passing accuracy in the game of football, this drill exercise can have the right influence on the accuracy of passing in the football game. In line with the title of the research that the researchers took, this study uses the Experiment method with the research design using one group pretest-posttest design, because to find out the influence and magnitude of the influence of the results of the research taken. The results of research conducted by researchers about the Effect of the Form of Drill Drill to the Wall on the Accuracy of Passing the Inside Foot of PERBI FC Football Players in football games, the amount of influence is 0.01.